Opportunities and challenges with improving biosecurity in aquaculture operations in the Global South - Verner-Jeffreys, David (WorldFish, 2025)
The presentation was presented at the International Workshop on Aquaculture Medicine & Aquatic Animal Health Management in Asia Pacific (AQUAMAP 2025). It discusses opportunities and challenges in enhancing biosecurity across aquaculture operations in the Global South, with a focus on Bangladesh. It outlines the drivers of disease emergence, such as live animal trade, poor regulation, and inadequate pathogen data. The work introduces a Participatory Biosecurity Gap Assessment (PBGA) and training module for finfish farms developed by WorldFish, the Department of Fisheries, FAO, BFRI, and CEFAS. Pilot assessments in Mymensingh identified twelve key pathogen pathways and potential biosecurity improvements. The study emphasizes equity, recognizing the need for inclusive, practical biosecurity processes that avoid excluding smallholder farmers, and promotes building resilience through education, diagnostics, vaccination, and better management practices.